Thomas & friends. Tales from the tracks - Awdry, W.; Asquith, Steve; Allcroft, Britt; Hit Entertainment; Twentieth Century Fox Home Entertainment, Inc. (Allen, TX : Hit Entertainment ; Beverly Hills, Calif. : Distributed by 20th Century Fox Home Entertainment, 2006)
Ride the rails as Thomas & Friends steam through the Island of Sodor. There's excitement around every bend in six stories from the Number 1 Engine.
Thomas and the birthday picnic -- Flour power -- The magic lamp -- Keeping up with James -- Tuneful toots -- Thomas tries his best.
Full screen (1.33:1) presentation
Title from container.
Created by Britt Allcroft.
Based on the Railway series by The Reverend W. Awdry.
Special features: Fun & games: "Arthur's tricky travels", "Spot the difference" and "Getting up Gordon's Hill"; Songs and more; Percy and the oil painting read-along; HIT extras.
Storyteller, Michael Brandon.
Keywords: Thomas the Tank Engine (Fictitious character) -- Juvenile drama; Thomas the Tank Engine (Fictitious character) -- Drama; Animated television programs; Television programs for children; Films for the hearing impaired